PRINCIPAL’S STRATEGY IN DEVELOPING STUDENT DISCIPLINE AT STATE MIDDLE SCHOOL 3 BONTONOMPO, GOWA REGENCY - Nurul Anggraeni; Ardiansyah; Sumarlin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of this study was to determine the principal's strategy in fostering student discipline and what are the supporting and inhibiting factors. This research approach is qualitative with a descriptive qualitative research format. The data sources for this study were the principal, vice principal for student affairs and homeroom teachers. Data collection techniques were in the form of observation, interviews and documentation. The results of this study are the principal's strategy in fostering student discipline. The results of this study are the principal's strategy in fostering student discipline, namely. a) Enforcing clear rules consistently and comprehensively which are marked by several clear rules posted in the classroom and understanding what is prohibited in the school. b) Providing examples and behaving positively at school such as arriving on time, dressing neatly when entering the classroom, and picking up and shaking hands with students in the morning. c) Availability of counseling services carried out by BK in fostering student discipline character such as direct guidance to students who violate and home visits. d) Giving awards and rewards to students who excel, exemplary students, and inspired students during the flag ceremony. e) Parent-student association program and community policing involvement in fostering student discipline such as using a perspective approach. The inhibiting factor is a strong environmental change because students come from different family backgrounds.